Mobile or hostile? Using smartphones in learning English as a foreign language1. Issue 5 (4th July 2022) - Şad, Süleyman Nihat; Özer, Niyazi; Yakar, Ümit; Öztürk, Fatih
Abstract: The purpose of this paper is to investigate the views of freshmen on using their smartphones in learning English as a foreign language. The study was designed based on a quantitative associational model. The data were collected from the 428 freshmen attending the English preparation programs run at İnönü and Fırat Universities, Turkey, using "Smartphone Use in Learning Foreign Language Scale". The results showed that participants use their smartphones more frequently to engage in English listening and speaking activities than reading and writing activities. The participants also believe that smartphones scarcely have adverse effects on learning English. However, it was also found that the more time students spend online, the more they suffer from the adverse effects of smartphones in terms of language learning. Results about gender revealed that female students use their smartphones more frequently than their male peers to engage in formal language learning activities. Significant differences related to frequency of smartphone use for both formal and informal language learning purposes were detected, with the Business Administration and Molecular Biology and Genetics department students showing higher frequency. No statistically significant difference was found between students' views about using smartphones for language learning according to the types of Internet connection (Wi-Fi, mobile data, or both).